Face-work in North American Presidential Debates: A Corpus-based Multi-theoretical Approach - Rosa María Martínez Abellán (Revista Alicantina de Estudios Ingleses)
As inherently confrontational contexts, North American presidential debates compel politicians to engage in image restoration efforts when targeted by a face-threatening act. Since the first televised debates in 1960, presidential campaigns have become increasingly mediatized and the need to defend against face-damage has increased, for there is still a need to uphold a favorable presidential image despite the prominence of impoliteness in these events. Although a longstanding tradition, there is still no framework for the combined analysis of threatening and defensive face-work in presidential debates. This paper presents a corpus-based three-fold analysis blending qualitative, quantitative and statistical methodologies to observe the evolution of facework in this context, focusing on impoliteness and image restoration manifestations. The selected corpus comprises the presidential debates of seven North American elections —one per decade—, providing an overview of the evolution of both phenomena. This methodology also allows insight into the frequency of specific strategies. The analysis adopts a multi-theoretical approach to demonstrate the effectiveness of integrating Impoliteness theory (Culpeper, 1996) and Image restoration theory (Benoit and Wells, 1996) to create a comprehensive new approach to the study of face-work in presidential debates. Supported by results from Pearson’s Chi-square test, the combination of these theories was shown to be possible. The recurrence of attack-defense pairings integrating strategies from both theories also pointed to their necessary combination. While the recent incorporation of a female presidential candidate hinted at the potential gender variation of face-work in the debates, further data is needed to obtain conclusive results.